2023
DOI: 10.1115/1.4063775
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Dynamic Behavior of Conventional and Pressure Relieving Brush Seals

Joshua P. Bowen,
Joshua J. Bird,
Harry Cross
et al.

Abstract: Brush seals consist of a static ring of densely packed, flexible, fine wire bristles that provide resistance to the flow. Pressure relieving brush seals can be employed to overcome issues such as hysteresis that affect seal durability by reducing friction between the bristle pack and back plate surface. The impact of such designs on the fluid dynamic behaviour of brush seals was studied following a concomitant methodology that exploited the benefits of both engine representative and large-scale testing facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Manuel et al [3] studied the influence of fence heights on the stiffness, leakage rate, and friction loss of brush seals and concluded that the fence's height is essential for the brush seal. Bowen et al [4,5] constructed a large-scale brush seal to study flow characteristics and pressure distributions in the bristle pack, and the results can be used in the establishment of porous medium models. Markus [6] designed a test rig to study the friction heat of brush seals, and the test rig can measure the temperature can be used in the establishment of porous medium models.…”
Section: Introductionmentioning
confidence: 99%
“…Manuel et al [3] studied the influence of fence heights on the stiffness, leakage rate, and friction loss of brush seals and concluded that the fence's height is essential for the brush seal. Bowen et al [4,5] constructed a large-scale brush seal to study flow characteristics and pressure distributions in the bristle pack, and the results can be used in the establishment of porous medium models. Markus [6] designed a test rig to study the friction heat of brush seals, and the test rig can measure the temperature can be used in the establishment of porous medium models.…”
Section: Introductionmentioning
confidence: 99%